Nursing care of a patient with constipation after surgery of thoracic vertebra compression fracture treated by midnight-noon ebb-flow acupiont application combined with Chinese herbal medicine hot compress (子午流注择时穴位贴敷联合中药热奄包改善1例胸椎压缩性骨折术后患者便秘的护理体会) - FAN Weiwei (范薇薇); WANG Qiujie (王秋洁) (中西医结合护理)
This paper summarized the nursing practice of a patient with constipation after surgery of thoracic vertebra compression fracture treated by midnight-noon ebb-flow acupiont application combined with Chinese herbal medicine hot compress. Based on the comprehensive nursing assessment, targeted nursing interventions on pain, postoperative constipation, anxiety and potential complications were carried out. In addition, Traditional Chines medicine nursing techniques such as midnight-noon ebb-flow acupiont application combined with Chinese herbal medicine hot compress were conducted to relieve the constipation symptoms and improve the recovery of the patient. (本文总结子午流注择时穴位贴敷联合中药热奄包改善1例胸椎压缩性骨折术后患者便秘的护理体会。护理人员积极开展护理评估, 明确护理要点, 根据患者疼痛、便秘、焦虑、潜在并发症等主要问题进行护理干预, 并配合穴位贴敷、中药热奄包热敷等中医护理适宜技术, 改善患者便秘症状, 减轻疼痛, 促进其早期康复。)